Fostering Employee Engagement through Organizational Climate and Reward Systems: Exploring the Mediating Role of Work-Life Balance and Employee Satisfaction among Millennial Employees in the Property Industry - Yohanes Andika Fajar Abadi; Tony Antonio (Dinasti Publisher, 2024)
Companies are increasingly concerned about millennials due to their growing presence in the workplace and their distinct perspectives compared to previous generations. In the property industry, a highly competitive and dynamic sector, attracting and retaining talent is a significant challenge for many companies. A positive organizational climate and an effective reward system are crucial to achieving company goals. When employees are content with the reward system and organizational climate, it leads to higher employee engagement, which can drive the achievement of organizational objectives. This study explores the relationship between the reward system and organizational climate in promoting employee engagement, with work-life balance and employee satisfaction mediating at PT. X, a company in the property industry. The research is based on a survey of 109 millennial employees working at PT. X. Employee satisfaction serves as a mediator for the impact of the reward system on employee engagement and mediates the effect of organizational climate on employee engagement. Companies are increasingly concerned about millennials due to their growing presence in the workplace and their distinct perspectives compared to previous generations. In the property industry, a highly competitive and dynamic sector, attracting and retaining talent is a significant challenge for many companies. A positive organizational climate and an effective reward system are crucial to achieving company goals. When employees are content with the reward system and organizational climate, it leads to higher employee engagement, which can drive the achievement of organizational objectives. This study explores the relationship between the reward system and organizational climate in promoting employee engagement, with work-life balance and employee satisfaction mediating at PT. X, a company in the property industry. The research is based on a survey of 109 millennial employees working at PT. X. Employee satisfaction serves as a mediator for the impact of the reward system on employee engagement and mediates the effect of organizational climate on employee engagement.